Effects of dietary protein-energy level on the survival, growth and body composition of tinfoil barb, barbonymus schwanenfeldii fry - Kamarudin, M.S.; Nuruljannah, M.P.; Syukri, F.; Cruz, C.R. (Green Wave, 2023)
An 8-week feeding trial was conducted to study the effects of dietary protein-energy level on the survival, growth, and body composition of tinfoil barb, Barbonymus schwanenfeldii fry. Fry (0.70±0.02 g) were randomly stocked in 60 L glass aquaria at 25 fish per aquarium. Six test diets were formulated to contain 40, 45, and 50 % protein with 17 and 18 kJ g-1 gross energy. Each diet was randomly assigned to three replicate aquaria, and fish were fed twice a day until satiation. Fish survival was not affected by the dietary protein, energy level, and their interaction. The results showed that higher dietary energy did not have significant effects on weight gain, specific growth rate, and feed efficiency of tinfoil barb. However, dietary protein had significant effects on fish growth and feed efficiency, while its interaction with energy had significant effect on growth. All dietary fed groups did not have histopathological changes in the liver and intestine. Fish fed 50% protein and 17 kJ g-1 gross energy showed significantly highest (p<0.05) specific growth rate compared to fish fed with 40% protein and 17-18 kJ g-1 gross energy.